The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1136/emermed-2018-207802
|View full text |Cite
|
Sign up to set email alerts
|

Defining significant childhood illness and injury in the Emergency Department: a consensus of UK and Ireland expert opinion

Abstract: BackgroundClarifying whether paediatric early warning scores (PEWS) accurately predict significant illness is a research priority for UK and Ireland paediatric emergency medicine (EM). However, a standardised list of significant conditions to benchmark these scores does not exist.ObjectivesTo establish standardised significant illness endpoints for use in determining the performance accuracy of PEWS and safety systems in emergency departments (ED), using a consensus of expert opinion in the UK and Ireland.Desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The differences between the opinions of the non-consensus patient cases were echoed in the wide range of median scores in the responses, which ranged from 1 (strongly disagree) to 8 (agree). This complexity was also highlighted in a study by Lillitos et al , 22 who aimed to establish a benchmark list defining significant acute paediatric conditions that warrant acute hospital admission from the emergency department, using a Delphi method. They failed to achieve consensus on 37 statements because assessment of sick children’s conditions may vary and depend on many factors, such as the healthcare professional’s experience and the child’s clinical presentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences between the opinions of the non-consensus patient cases were echoed in the wide range of median scores in the responses, which ranged from 1 (strongly disagree) to 8 (agree). This complexity was also highlighted in a study by Lillitos et al , 22 who aimed to establish a benchmark list defining significant acute paediatric conditions that warrant acute hospital admission from the emergency department, using a Delphi method. They failed to achieve consensus on 37 statements because assessment of sick children’s conditions may vary and depend on many factors, such as the healthcare professional’s experience and the child’s clinical presentation.…”
Section: Discussionmentioning
confidence: 99%
“…They failed to achieve consensus on 37 statements because assessment of sick children’s conditions may vary and depend on many factors, such as the healthcare professional’s experience and the child’s clinical presentation. In the study by Lillitos et al , 22 the authors identified many neutral answers in round 1 and therefore added the response category ‘I don’t look after children with this condition’. We also identified many patient cases in which the healthcare professionals did not have sufficient experience to answer the question, which underscores the complexity of paediatrics.…”
Section: Discussionmentioning
confidence: 99%
“…An obvious omission is comparison of Paediatric Early Warning Scores (PEWS) between groups. Currently, there is no consensus nationally on PEWS observations and scoring,21 22 so this analysis was not performed. Finally, due to the descriptive focus of this study, we have not used multiple-testing corrections, so significant comparisons must be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…There is no existing gold-standard outcome measure for the decision to admit or discharge a child or young person from the ED, 5 and the decision to admit is a complex one, which can vary between clinicians and hospitals. One EWS system, the Paediatric Observation Priority Score (POPS), recommended by the Intercollegiate Committee for Standards for Children and Young People in Emergency Care Settings 6 has shown initial promise in aiding recognition of unwell children but also aiding safe discharge decisions.…”
mentioning
confidence: 99%